Growing Cities, Growing Food: Urban Agriculture on the Policy Agenda - Gundel, Sabine; Dubbeling, Marielle; Zeeuw, Henk de; Bakker, Nico; Sabel-Koschella, Ulrich (Deutsche Stiftung fur internationale Entwicklung (DSE), 2000)
The first part of these proceedings contains papers addressing such themes as the impact of urban agriculture on households, policy options ... Part 2 contains city case studies from Africa, Latin America, Asia and Europe.